2010
DOI: 10.1177/0741932510361264
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Work Conditions Among Early Career Special Educators in High- and Low-Poverty Districts

Abstract: The authors used teacher data from the Study of Personnel Needs in Special Education to compare the district and school supports, work manageability, professional development, and induction of early career special educators in high- and low-poverty districts. Teachers in high-poverty districts reported less desirable work conditions than their counterparts in more affluent districts. When compared to teachers in low-poverty districts, those in less affluent districts viewed their principals and colleagues as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 58 publications
3
53
0
Order By: Relevance
“…Using national data from the School and Staffing Survey, Mason-Williams (2015) found that SETs in high-poverty schools were less likely to have teaching experience, a master's degree or higher, and certification in content areas. Fall and Billingsley (2011) found similar patterns for SETs in high-poverty districts using data from the Study of Personnel Needs in Special Education. However, the extent to which SETs are distributed along other important school characteristics, such as racial composition and achievement level, is unknown.…”
Section: Distribution Of Setsmentioning
confidence: 59%
“…Using national data from the School and Staffing Survey, Mason-Williams (2015) found that SETs in high-poverty schools were less likely to have teaching experience, a master's degree or higher, and certification in content areas. Fall and Billingsley (2011) found similar patterns for SETs in high-poverty districts using data from the Study of Personnel Needs in Special Education. However, the extent to which SETs are distributed along other important school characteristics, such as racial composition and achievement level, is unknown.…”
Section: Distribution Of Setsmentioning
confidence: 59%
“…Rather, the shortage of qualified, prepared special educators available to work with students with specific disabilities, including emotional/behavioral disorders (EBDs), autism, and intellectual disabilities, as well as regional variations have been noted (Bowen & Klass, 1993; Lauritzen & Friedman, 1991, 1993; McLeskey, Tyler, & Flippin, 2004). More recently, evidence emerged that students with disabilities in high-poverty schools and districts were more likely to be taught by individuals with lesser qualifications and preparation (Fall & Billingsley, 2011; Mason-Williams, 2015), supporting what many researchers have long suggested: Teacher shortages and higher rates of attrition more often affect schools with high concentrations of poor and minority students and in exclusionary school settings (Boe, deBettencourt, Dewey, Rosenberg, Sindelar, & Leko, 2013; Brownell, Rosenberg, Sindelar, & Smith, 2004; McLeskey et al, 2004).…”
Section: Insufficient Supply and Attrition In Special Educationmentioning
confidence: 78%
“…Theoretically, collaboration, mutual planning time, and shared responsibilities among special and general educators should help to meet the needs of students placed in classrooms with general educators with limited preparation in special education. However, emerging research evidence on working conditions suggests this does not happen (Bettini, Crockett, Brownell, & Merrill, 2016; Fall & Billingsley, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novice special education teachers (SETs; those in their first 3 years) consistently report their workloads are unmanageable (Bettini et al, 2017; Fall & Billingsley, 2011; Mathews, Rodgers, & Youngs, 2017). For example, in a nationally representative survey, more than 75% of novice SETs said routine duties interfered with teaching, and more than 25% said workloads were “not at all” manageable (Billingsley, Carlson, & Klein, 2004).…”
mentioning
confidence: 99%